Literature Review: Pengaruh Terapi Musik Terhadap Lama Persalinan Kala I Fase Aktif - Lilik Indahwati; Devi Rizka Rahmawati; Mega Ulfah (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Psychological factors can influence the progress of the labor process. Music therapy is preferred as a non-pharmacological intervention because it has no side effects and benefits as self-hypnosis. This study aims to decide the effect of music therapy on the duration of labor during the active phase. Through the research design using literature research (literature review). Sources of data obtained through analysis of 11 journals through national and international database searches, in the last 10 years (2010-2020), using quality assessment methods and PICOT. The results obtained showed that music had an influence on the duration of labor during the active phase. This is possible due to adequate contractions caused by the workings of music which affect the hypothalamic system in the mother's brain, as a form of acceptance of the intervention given. It was concluded that music therapy has a significant effect on the duration of labor during the first active phase.